PENGEMBANGAN KARAKTER ANAK MELALUI PEMBELAJARAN ILMU SOSIAL - M. Miftah (Jurnal Pendidikan Karakter, 2013)
Abstrak: Karakter adalah cara berpikir dan berperilaku yang menjadi ciri khas tiap individu untuk hidup dan bekerja sama. Individu yang berkarakter baik adalah individu yang dapat membuat keputusan dan siap mempertanggungjawabkan akibatnya. Pembentukan karakter merupakan amanah UU Sisdiknas Tahun 2003 agar pendidikan tidak hanya membentuk insan Indonesia yang cerdas, namun juga berkepribadian atau berkarakter sehingga dapat melahirkan bangsa yang berkarakter dan bernafas nilai-nilai luhur bangsa dan agama. Memahami pendidikan karakter adalah pendidikan budi pekerti plus, yaitu yang melibatkan aspek pengetahuan, perasaan, dan tindakan. Hal ini kini menjadi perhatian serius pemerintah untuk mengupayakan perbaikan kualitas pendidikan di Indonesia. Pembelajaran ilmu sosial menjadi salah satu alternatif dalam upaya mengembangkan, membina karakter dan menjadikan martabat bangsa yang dapat dibanggakan di hadapan bangsa lain. Kata Kunci: pendidikan karakter, pembelajaran ilmu sosial, kualitas pendidikan CHARACTER DEVELOPMENT OF CHILDREN LEARNING THROUGH SOCIAL SCIENCE Abstract: The character is a way of thinking and behaving that characterizes each individual to live and work. Individuals who are individuals of good character who can make decisions and be prepared to account for any effect of the decisions he has made. Formation of character is one of the national education goals. Amanah Education Law of 2003 was intended to be educational not only establish Indonesia smart man, but also personality or character, so it will be born generation of people who grew up with the characters that breathe the noble values of the nation and religion. Understanding the character education is a plus character education, which involves aspects of knowledge (cognitive), feeling (feeling), and action (action). This issue is a serious concern for the government at this time, the relentless government make efforts to improve the quality of education in Indonesia, but not everything works out, especially Indonesia produces human character. The article was written with the purpose to share thoughts, and a hope for the author to the executive educator/teacher/policy makers that, for order to realize the above education is an alternative learning social studies in an effort to develop, nurture character/moral values and making the dignity of the nation to be proud of in front of other people. Keywords: character education, social sciences learning, eduation quality